Journal of Garden History. (Londen : The Garden Trust, 1969)
“Garden History is one of the foremost journals in its field worldwide and remains the journal in which to be published for those dedicated to garden history scholarship. It has a wide academic and professional readership, and from the earliest issue to the present is an enormously important and relevant source of information, providing vital support to the Gardens Trust’s promotion of the study of garden history, landscape gardening and horticulture. Its reviews section also offers timely and critical reflection upon recent published work in the field. (https://thegardenstrust.org/research/journal/)
Https://thegardenstrust.org/research/journal/ (registers)
Engels
Tijdschriften
Keywords: tuin; geschiedenis